High levels of biomarkers of collagen remodeling are associated with increased mortality in COPD – results from the ECLIPSE study. Issue 1 (December 2016) - Sand, Jannie; Leeming, Diana; Byrjalsen, Inger; Bihlet, Asger; Lange, Peter; Tal-Singer, Ruth; Miller, Bruce; Karsdal, Morten; Vestbo, Jørgen
Abstract Background There is a need to identify individuals with COPD at risk for disease progression and mortality. Lung tissue remodeling is associated with the release of extracellular matrix (ECM) fragments into the peripheral circulation. We hypothesized that ECM remodeling was associated with mortality in COPD and measured neo-epitopes originating from ECM proteins associated with lung tissue remodeling. Methods Biomarkers of ECM remodeling were assessed in a subpopulation (n  = 1000) of the Evaluation of COPD Longitudinally to Identify Predictive Surrogate End-points (ECLIPSE) cohort. Validated immunoassays measuring serological neo-epitopes produced by proteolytic cleavage associated with degradation of collagen type I, III, IV, and VI, elastin, and biglycan, and formation of collagen type VI as well as fibrinogen and C-reactive protein were used. Multivariate models were used to assess the prognostic value of these biomarkers. Results Thirty subjects (3.0 %) died during follow-up. Non-survivors were older, had reduced exercise capacity, increased dyspnea score, and included fewer current smokers. All collagen biomarkers were significantly elevated in non-survivors compared to survivors. Mortality risk was significantly increased for subjects with collagen remodeling biomarkers in the upper quartile, especially for the degradation fragment of collagen type IV C6M (hazard ratio 6.6 [95 % confidence interval 2.9-15.2], P  < 0.0001) after adjusting for relevant confounders. Conclusions Serological biomarkers of collagen remodeling were strongly associated with mortality in subjects with COPD indicating that assessment of tissue turnover in the parenchyma and small airways may be useful in the prognosis of COPD. Trial registration NCT00292552, GSK Study No. SCO104960.